Homeland. The complete first season [videorecording (DVD)] - Gordon, Howard, 1961-; Gansa, Alex; Danes, Claire, 1979-; Lewis, Damian, 1971-; Baccarin, Morena; Patinkin, Mandy; Harewood, David; Raff, Gideon (20th Century Fox Home Entertainment, 2012)
Carrie Mathison, a brilliant but volatile CIA agent, suspects that a rescued American POW may not be what he seems. Is Marine Sgt. Nicholas Brody a war hero or an Al Qaeda sleeper agent plotting a spectacular terrorist attack on U.S. soil? Following her instincts, Mathison will risk everything to uncover the truth - her reputation, her career, and even her sanity.